Allylic and Retro‐Allylic Rearrangements upon Bromination of 8, 9‐Substituted 4, 4, 6‐Trimethyl‐4H‐Pyrrolo[3, 2, 1‐ij]Quinoline‐1, 2‐Diones. New Aspects and Synthetic Applications. Issue 1 (2nd January 2023) - Novichikhina, Nadezhda P.; Pantykina, Diana A.; Shestakov, Alexander S.; Potapov, Andrey Yu.; Ledenyova, Irina V.; Kuznetsov, Mikhail A.; Shikhaliev, Khidmet S.
Abstract: Bromination of 4, 4, 6‐trimethyl‐4 H ‐pyrrolo[3, 2, 1‐ ij ]quinoline‐1, 2‐diones containing an allylic moiety with N ‐bromosuccinimide (NBS) in carbon tetrachloride in the presence of benzoyl peroxide (BPO) and in DMF solution were studied. When using an equimolar amount of NBS in the BPO‐CCl4 system, the reaction proceeds regioselectively and standardly at the methyl group at position 6 with the formation of 6‐bromomethylene derivatives. In the NBS‐DMF system, monobromination proceeds at position 5 with the migration of a multiple bond by the allylic rearrangement. With a twofold excess of NBS, in both cases a ( Z )‐5‐bromo‐6‐bromomethylene derivative is formed. The 5‐monobromine isomers undergo retro‐allylic rearrangement in N ‐ and S ‐alkylation reactions, resulting exclusively in 6‐ N ‐alkyl and 6‐ S ‐alkyl derivatives, respectively. Similar products are formed by the same reactions with the use of 6‐bromomethylene derivatives. Abstract : The features of bromination of 4, 4, 6‐trimethyl‐4 H ‐pyrrolo[3, 2, 1‐ ij ]quinoline‐1, 2‐diones (PQD) containing allyl fragment with N ‐bromosuccinimide (NBS) under radical and electrophilic conditions were studied in detail. Unusual facts of allyl rearrangement during bromination of PQD in the NBS‐DMF system and retro‐allyl rearrangement during alkylation of N ‐ and S ‐nucleophiles obtained by 5‐bromo‐PQD were established.